2019
DOI: 10.1108/ijqss-08-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of alternative measures of telecommunications service quality

Abstract: Purpose The purpose of this paper is to review the service quality (SQ) models established in various empirical studies conducted across the world specifically applied to telecommunications services. Design/methodology/approach This paper examines different SQ models reported in the literature applicable to the telecommunications sector. The selected 29 studies were limited to empirical English studies based on survey data and statistical methods of analysis and having the SQ construct defined from the custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Literature review 2.1 After sales service quality Importantly, the service quality (SQ) may only be gauged when the service has actually been rendered/delivered (Losada-Otalora et al, 2021). This is why researchers in the past have looked to elaborate upon its relation to an organization's overall performance, which includes its profitability, stemming from both CS and CL (Abd-Elrahman et al, 2020). Furthermore, significant research has been done, reporting the causal connection between SQ and CS (Slack et al, 2020;Pantouvakis and Karakasnaki, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Literature review 2.1 After sales service quality Importantly, the service quality (SQ) may only be gauged when the service has actually been rendered/delivered (Losada-Otalora et al, 2021). This is why researchers in the past have looked to elaborate upon its relation to an organization's overall performance, which includes its profitability, stemming from both CS and CL (Abd-Elrahman et al, 2020). Furthermore, significant research has been done, reporting the causal connection between SQ and CS (Slack et al, 2020;Pantouvakis and Karakasnaki, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the technology-based nature of telecommunication, human-to-human (i.e. service providers and customers) interaction is insufficient to explain customers’ perception of telecommunication quality (Abd-Elrahman et al , 2019). Some studies revealed that the service quality of mobile telecommunication providers is multi-dimensional (Kim et al , 2004; Santouridis and Trivellas, 2010).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Stability, transmission speed and network coverage are the core attributes of network quality. Breaks in Internet connectivity can lead to poor perceptions of network quality from the customer's perspective (Abd-Elrahman, Hassan, El-Borsaly, & Hafez, 2019).…”
Section: Attributes Of Internet Service Packagesmentioning
confidence: 99%
“…Stability, transmission speed and network coverage are the core attributes of network quality. Breaks in Internet connectivity can lead to poor perceptions of network quality from the customer’s perspective (Abd-Elrahman, Hassan, El-Borsaly, & Hafez, 2019). Network quality helps to create the necessary competitive advantage for ISPs by being an effective differentiating factor (Oluwafemi & Adebiyi, 2018; Santouridis et al.…”
Section: Literature Reviewmentioning
confidence: 99%